Optimizing Track Infrastructure Availability - Mlinarić, Tomislav Josip; Pirnar, Miran (Promet - Traffic&Transportation, 2012)
Failure to realize the schedule which is primarily reflected in train delays is the direct consequence of insufficient availability of capacities of the current railway infrastructure which are generated by low level of usable quality of the track network in general. The aim of the research presented in this paper is to determine the method of optimal interventions of the rail infrastructure managers and traffic control activities on the reduction of the influence of slow runs and line closures thus ensuring a sufficient number of rail routes for the customers’ needs and consequently higher quality realization of the schedule. The paper gives a concrete presentation of the volume of slow runs and line closures, calculation of reducing the level of railway capacities with a simulation and the result of this condition on the capacity of the concrete railway line and the proposal of a model for organizing an expert group within the traffic control activities for the fastest possible elimination of these negative phenomena. KEY WORDS: liberalization, route leasing, quality deterioration, track availability